Studies on Wear Behaviour of Aluminium 6061Alloy Reinforced with B4C & Mica Particulates Hybrid Metal Matrix Composite - K. Arumugam, Dr; Sathiyamoorthy, V; Jerome Kingston, J; akiraman, K; V, Senthilkumar; Suresh, R (International Journal of Engineering and Technology, 2018)
Hybrid Metal matrix composites are commonly used in Aerospace, Automobile industries because of its light weight, High tensile strength, high resistance to wear and improved specific strength. This is mainly due to improved mechanical and tribological properties like strength, stiffness, abrasion, impact resistance and wears resistance. In the present scenario, a lot of research activities were on automobile. This paper direct the researchers and engineer towards suitable selection of materials by its properties in the relevant area and various Â techniques involved in fabrication of metal matrix composites, predominantly on the liquid state metal processing method. In this work Al6061, Boron carbide, mica and hybrid Aluminium metal matrix composites are fabricated using Stir casting Techniques with varying mass fraction of mica 3%, 4%, 5% incorporated into the alloy, Sustaining the mass fraction of boron carbide asÂ  10% for all proportions. Mica and B4C ceramic particles were incorporated into Al 6061 alloy by stir-casting method. In Stir casting method of composite materials synthesis, a dispersed phase (ceramic particles, short ï¬bers) is mixed with a molten metal matrix by means of mechanical stirring. The samples were studied using scanning electron microscope (SEM) one of the most useful instrument for future research to know its microstructure. This study emphasize on the dry siding wear behaviour of aluminium reinforced with 3%,4%,5% mica and constant quantity of 10% boron carbide hybrid composite using a pin on disc. Wear performance of the hybrid composites were evaluated over a different load ranges and at different sliding velocities.Â Â
Keywords: Hybrid metal matrix; Al 6061; B4C; Mica; Stir casting; SEM; Pin on disc [Tribometer].